Neuroprotective Effect of Memantine on Hippocampal Neurons in Infantile Rat Hydrocephalus - (:unkn) unknown (TURKISH NEUROSURGICAL SOC, 2011)
AIM:The effect of memantine administration on hippocampal neurons of the infantile rats with kaolin induced hydrocephalus was investigated. MATERIAL and METHODS: Hydrocephalus was induced by injecting kaolin into the cisterna magna of 3-weeks old Sprague-Dawley rat pups. One group received a single daily dose of 20mg/kg memantine i.p. following hydrocephalus induction for a period of two weeks. By the end of the two-week period, animals were radiologically evaluated by magnetic resonance imaging and then sacrificed to get their cerebrums removed. Both immunohistochemical analysis of nitric oxide synthase activity and quantification of spared neurons in CA1, CA2 and CA3 regions of hippocampus were performed. RESULTS: In hydrocephalus-induced rats considerable neuronal loss associated with significantly increased nitric oxide synthase immunoreactivity were determined in all hippocampal regions. However, memantine treated rats showed significantly higher number of spared neuron counts and reduced nitric oxide synthase immunoreactivity in CA1 and CA2 regions compared with the non-treated rats. CONCLUSION:The findings of the study show that hippocampal neurons may constitute important targets for injury secondary to hydrocephalic process in experimental infantile hydrocephalus. Early anti-excitotoxic treatment with memantine seems to have a neuroprotective effect especially in the CA1 and CA2 subunits of the hippocampus.
Keywords: Hippocampus; Hydrocephalus; Memantine; Neuroprotection; Rat; KAOLIN-INDUCED HYDROCEPHALUS; CHANNEL BLOCKER MEMANTINE; GERBIL HIPPOCAMPUS; NMDA RECEPTOR; ISCHEMIA; MODEL; ANTAGONIST; PATHOLOGY; BENEFIT; RABBIT